Pengembangan Pembelajaran Fisika Berbasis Proyek untuk Meningkatkan Keterampilan Proses Sains: Systematic Literature Review - Nabila El Shofy; Sri Jumini (Jurnal Kridatama Sains dan Teknologi, 2026)
This study aims to synthesize and analyze various strategies for enhancing Science Process Skills (SPS) in physics education based on a literature review of several previous research findings. Science process skills are a key element in physics learning that views science not only as a product of facts and theories but also as a research process through observation and experimentation. The method used in this article is a systematic literature review by analyzing 15 research articles covering the use of learning models such as Problem-Based Learning (PBL), guided inquiry, STEAM, and the utilization of digital media such as e-modules. According to Rachmat Rizaldi, the results of the analysis indicate that the application of active learning models significantly improves students' SPS with varying effectiveness scores, where the use of PBL-based e-modules recorded an effectiveness score of 75.41. Furthermore, a positive correlation was found between school accreditation status and students' SPS achievement levels, with A-accredited schools showing higher performance compared to B and C-accredited schools. This study concludes that the integration of innovative learning models, digital media, and the development of scientific attitudes is the most effective strategy to optimize SPS. The implications of this research are expected to serve as a reference for educational practitioners in designing more adaptive and comprehensive physics learning tools.